Role of fixed-dose combinations of antibiotics and steroids in ophthalmic surgery - V.P. Nikolaenko; D.F. Belov (РМЖ "Клиническая офтальмология")
V.P. Nikolaenko1,2, D.F. Belov1 1City Multidisciplinary Hospital No. 2, St. Petersburg, Russian Federation 2St. Petersburg State University, St. Petersburg, Russian Federation This paper reviews the relevance of fixed-dose combinations (FDC) of antibiotics (AB) and steroids in cataract surgery. Postoperative pharmacotherapy of phacoemulsification addresses two main issues — reducing inflammation and preventing infectious complications. Therefore, the question arises about the role of FDCs of ABs and steroids addressing both issues but in compliance with baseline principles. The most effective measure to prevent acute endophthalmitis is an intracameral injection of antibiotics at the end of surgery. Meanwhile, as early as after 10 hours, drug concentration reduces to a level that fails to prevent aqueous humor contamination with bacteria. Therefore, topical ABs, either monotherapy or FDC, are reasonable up to complete healing of phaco incisions (approximately after one week). The authors suggest a postoperative management algorithm after uneventful phaco involving topical administration of an FDC containing 0.5% levofloxacin and 0.1% dexametha sone QID at week 1. If inflammation (conjunctival redness and cells/flare) persists, switching to dexamethasone as monotherapy QID during week 2 (and withdrawal without tapering) is recommended. Keywords: phacoemulsification, endophthalmitis, prevention, inflammation, antibiotic, steroid, dexamethasone, fixed-dose combination, eye drops, withdrawal syndrome. For citation: Nikolaenko V.P., Belov D.F. Role of fixed-dose combinations of antibiotics and steroids in ophthalmic surgery. Russian Journal of Clinical Ophthalmology. 2022;22(1):58–61 (in Russ.). DOI: 10.32364/2311-7729-2022-22-1-58-61.